Participatory Budgeting in Hrubieszów, Poland, as an Example of Residents’ Sustainable Participation in Shaping Public Expenditure - Sroka, Jacek; Pawlica, Beata; Ufel, Wojciech (Studia z Polityki Publicznej, 2024)
The article contains a case study of residents’ participation in the process of shaping the city’s public expenditure through participatory budgeting. The case of Hrubieszów deserves a closer look due to the pro-participatory attitude of a significant number of the city’s officials, social activists, and residents. There is also a certain level of enthusiasm, despite the fact that participatory budgeting arrived in the city relatively late – in 2017. This article presents the functioning of this process both from the perspective of the local authorities and officials, as well as the project applicants and residents involved in the process. The focus of analysis is on local signs of readiness to cooperate which, in favorable conditions, focus on “deliberative moments” and are followed by a “deliberative stance,” constituting a basis for pro-participation activities.